2002
DOI: 10.1097/00043426-200206000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Pediatric Neuroblastoma With Tumor Thrombus in the Inferior Vena Cava

Abstract: The authors describe two children with abdominal neuroblastoma with radiographic evidence of tumor extension into the inferior vena cava. Imaging studies were suggestive of Wilms tumor, but histologic analysis revealed neuroblastoma. In one patient a pulmonary embolus developed after initiation of cytotoxic therapy; the second patient was prophylactically anticoagulated and had no embolic event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…The peak incidence of neuroblastoma is at age 19 months and the distribution of cases by age clearly shows that this is a disease of infancy and early childhood (Brodeur et al 1988) while nephroblastoma are more frequently seen in children older than age 40 months. In neuroblastomas with thrombus in the vena cava, the age at diagnosis of the tumor is always older than in classical neuroblastoma (Bagatell et al 2002; Huang et al 2006; Day et al 1991; Mehta and Lim-Dunham 2003; Nagda et al 2005) as for the patient in the present cases not allowing the distinction between neuroblastoma and Wilms tumor. Moreover, some cases have been discovered in adults (Custodio et al 1999; Onishi et al 1988; Yashiro et al 1984).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The peak incidence of neuroblastoma is at age 19 months and the distribution of cases by age clearly shows that this is a disease of infancy and early childhood (Brodeur et al 1988) while nephroblastoma are more frequently seen in children older than age 40 months. In neuroblastomas with thrombus in the vena cava, the age at diagnosis of the tumor is always older than in classical neuroblastoma (Bagatell et al 2002; Huang et al 2006; Day et al 1991; Mehta and Lim-Dunham 2003; Nagda et al 2005) as for the patient in the present cases not allowing the distinction between neuroblastoma and Wilms tumor. Moreover, some cases have been discovered in adults (Custodio et al 1999; Onishi et al 1988; Yashiro et al 1984).…”
Section: Discussionmentioning
confidence: 64%
“…For nephroblastoma we have the detection of the renal origin of the tumor with the claw sign but sometime this sign missing. The calcifications are more frequent in neuroblastoma but calcifications are also seen in approximately 15% of Wilms (Bagatell et al 2002). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathology revealed neuroblastoma, which very rarely presents with tumor thrombus. In our review of the literature, we found only six cases of neuroblastoma with tumor thrombus and only 2 had atrial extension [7][8][9]. In patient 4, histology revealed CCSK.…”
Section: Discussionmentioning
confidence: 99%